A framework to lead Thai SMEs to fit international business requirement: Case study of Solution Ceramic Co., Ltd., Thailand - Soontarin Nupap (2018)
Recently, due to the financial crisis all over the world, the intensive competition in global market, lack of government and financial support, and non-using advanced technology, many small and medium sized ceramic enterprises (SMEs) in Lampang, Thailand have been closed down dramatically. This paper deals with the upgrading of Thai SMEs in order to meet with the international standards and business viability. Based on different tools and methodology applied, such as Business Planning, Product Lifecycle Management (PLM), Business Process Reengineering (BPR), and open source Enterprise Resource Planning (ERP), a proposed conceptual framework was developed for SMEs Business Life Cycle Management. The result of this research is expected to get a framework for preparing experienced SME before taking a loan from the banks or being registered to MAI. The framework is applied with the Intellectual Capital (IC) theory. Solution Ceramic Co., Ltd. is used as a case study for this work. © 2011 IEEE.